2022
DOI: 10.3389/fenvs.2022.939382
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater depth alters soil nutrient concentrations in different environments in an arid desert

Abstract: Soil nutrients are vital for plant growth and survival and present a crucial role in terrestrial function and productivity. However, little is known about the effect mechanism of groundwater table on soil nutrients in an arid desert ecological system. This study investigated the impacts of groundwater depth on the concentrations of soil organic carbon (C), available nitrogen (N), phosphorus (P), and potassium (K) at shallow groundwater depths (0.4, 0.8, 1.2, 1.8, and 2.2 m) and field deep groundwater depths (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Our results showed that deeper groundwater had a strong effect on soil total carbon, total nitrogen, available nitrogen, and available phosphorus contents. Previous studies reported that groundwater depth affects the soil nitrogen concentration, and the soil nitrogen concentration decreased with increasing groundwater depth ( Zhang et al., 2022 ). Our finding was related to the fact that the extent of soil nitrogen concentration that leached to the groundwater interface decreased with increasing depth, and this result is in accordance with many other studies ( Granlund et al., 2000 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our results showed that deeper groundwater had a strong effect on soil total carbon, total nitrogen, available nitrogen, and available phosphorus contents. Previous studies reported that groundwater depth affects the soil nitrogen concentration, and the soil nitrogen concentration decreased with increasing groundwater depth ( Zhang et al., 2022 ). Our finding was related to the fact that the extent of soil nitrogen concentration that leached to the groundwater interface decreased with increasing depth, and this result is in accordance with many other studies ( Granlund et al., 2000 ).…”
Section: Discussionmentioning
confidence: 94%
“…Soil nutrients have substantial effects on plant growth and play important roles in productivity and ecosystem functions ( Zhang et al., 2022 ). Soil carbon is essential for maintaining soil nutrients, which influence soil biotic and abiotic properties ( Ge et al., 2020 ; Cheng et al., 2021 ; Lyu et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tang et al (2023) suggest that the application of biochar 15 ~ 22.5 t hm −2 increased the adsorption capacity of NH 4 + –N by 0.3 ~ 1.0 mg kg −1 and reduced the N leaching flux by 16.8% ~ 33.2% in saline–alkaline land. In this experiment area in Tarim River Basin, under the conventional N with maize, the soil sand content is large and the fertilizer retention ability is poor, which creates a high risk of NO 3 − –N leaching in this area (Zhang, An, et al, 2022; Zhang, Zeng, et al, 2022). According to the Xinjiang Statistical Yearbook, the use of chemical fertilizers (especially N) has been increasing (Feng et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Soil carbon (C) and nitrogen (N) cycles are closely interlinked and play a vital role in the composition, structure and function of ecosystems (Bejarano et al, 2014; Liu et al, 2023). Labile fractions of C and N are strongly affected by exogenous N input and agronomic management practices, which affects the fluxes of CO 2 , N 2 O and CH 4 , that contribute between 14% and 17% to global anthropogenic GHG emissions (Zhang, An, et al, 2022; Zhang, Zeng, et al, 2022). The global average temperature is predicted to increase by 2°C by the end of the 21st century (IPCC, 2014), which could be attributed to atmospheric GHG emissions (Cuello et al, 2015; Tian et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This finding has been extensively documented that the increase in groundwater depth can result in the reduction of soil nutrients, degradation of soil structure, reduction in soil moisture content, and decline in soil functionality, all of which have a detrimental impact on soil microbial diversity and composition ( Prieto et al, 2012 ; Sun et al, 2020 ; Chen et al, 2021 ). Whereas, the impact of rising groundwater depth on soil microbiota has been relatively overlooked ( Zhang et al, 2022 ), and it has not been clearly defined whether the alterations in soil microbial diversity caused by increasing groundwater depth are associated with a decline in multiple soil functions. The depletion in soil total nitrogen, soil organic carbon, and soil moisture by increasing groundwater depth could directly resulted in the loss of microbial diversity because reduced soil resource availability constrains the microbial metabolism and composition, furthermore decreased their supports on soil multifunctionality ( Chen et al, 2020 ; Ye et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%